Microhabitat selection by three small mammal species in oak-elm forest - Miklós Peter; Žiak Dávid
Between 1996 and 1998, microhabitat selection by three small mammal species was studied in oak-elm forest using the catch-mark-release (CMR) method. Microhabitat selection by these species was assessed by Discriminant Function Analysis (DFA) and Canonical Correspondence Analysis (CCA). Apodemus flavicollis was shown to prefer dense young forest and shrubs, but the presence of dead woody material was also important. In Microtus arvalis the data confirmed a negative relationship with stands with higher tree and shrub cover and a preference for open meadows. Clethrionomys glareolus was found to prefer non-fragmented tree microhabitats, preferring sites with developed undergrowth and ample hiding places amongst fallen logs and branches. Although C. glareolus did not change its microhabitat requirements during the year (spring to autumn), within forest stands it was connected with undergrowth regardless of species composition; this highlights the importance of undergrowth for C. glareolus. Seasonal changes in microhabitat selection could not be confirmed unambiguously.